2016
DOI: 10.1038/srep36544
|View full text |Cite
|
Sign up to set email alerts
|

Probing the PI3K/Akt/mTor pathway using 31P-NMR spectroscopy: routes to glycogen synthase kinase 3

Abstract: Akt is an intracellular signalling pathway that serves as an essential link between cell surface receptors and cellular processes including proliferation, development and survival. The pathway has many downstream targets including glycogen synthase kinase3 which is a major regulatory kinase for cell cycle transit as well as controlling glycogen synthase activity. The Akt pathway is frequently up-regulated in cancer due to overexpression of receptors such as the epidermal growth factor receptor, or mutation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…PI3K/AKT signaling pathway plays critical roles in orchestrating multiple cellular functions 5 - 8 . Mammalian target of rapamycin (mTOR), as downstream effector of PI3K/AKT pathway, consists of two functionally distinct multi-protein complexes, mTOR complex 1 (mTORC1) and mTOR complex 2 (mTORC2), which were involved in protein synthesis, cell growth, autophagy, metabolism, and survival 5 - 8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PI3K/AKT signaling pathway plays critical roles in orchestrating multiple cellular functions 5 - 8 . Mammalian target of rapamycin (mTOR), as downstream effector of PI3K/AKT pathway, consists of two functionally distinct multi-protein complexes, mTOR complex 1 (mTORC1) and mTOR complex 2 (mTORC2), which were involved in protein synthesis, cell growth, autophagy, metabolism, and survival 5 - 8 .…”
Section: Introductionmentioning
confidence: 99%
“…PI3K/AKT signaling pathway plays critical roles in orchestrating multiple cellular functions 5 - 8 . Mammalian target of rapamycin (mTOR), as downstream effector of PI3K/AKT pathway, consists of two functionally distinct multi-protein complexes, mTOR complex 1 (mTORC1) and mTOR complex 2 (mTORC2), which were involved in protein synthesis, cell growth, autophagy, metabolism, and survival 5 - 8 . Since the PI3K/AKT/mTOR pathway is upregulated in almost all cancers, anticancer drugs including LY294002, MK2206, everolimus, rapamycin, and AZD8055 have been developed to target crucial kinases associated with this pathway 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PtdCho transfer protein (PC-TP) is involved in preserving steady-state membrane phospholipid content in cells in response to cellular lipid efflux. PC-TP is associated with the steroidal 31 P-NMR spectroscopy that can detect phospholipid metabolites in cells and cell extracts [ 15 , 16 ] and is clinically translatable [ 17 ]. Figure 4 (a) shows a 31 P-NMR spectrum acquired on an aqueous extract from untreated LNCaP cells.…”
Section: Resultsmentioning
confidence: 99%
“…Venkatesh et al [ 28 ] has also demonstrated that treatment with the PI3K inhibitor LY294002 and mTOR inhibitor everolimus decreased phosphocholine levels associated with decreased in choline kinase activity in glioblastoma cell lines. However other studies have shown that phosphocholine content of cancer cells isn’t consistently altered by treatment with PI3K/Akt/mTOR inhibitors [ 29 ].…”
Section: Discussionmentioning
confidence: 99%